QFD application using SERVQUAL for private hospitals: a case study - (:unkn) unknown (My University, 2013)
The purpose of this paper is to describe how quality function deployment (QFD) methodology was employed for translating customer needs and expectations into the quality characteristics in a private healthcare setting. This case study illustrates how an existing approach of SERVQUAL and QFD integration can be applied for quality improvement. Integrating SERVQUAL into QFD to set the success factors to improve quality in the healthcare industry is the main aim of this paper. A privatelyheld university hospital, within the city of Istanbul in Turkey, was selected as the sampling frame. A SERVQUALtype of questionnaire was used and a total of 250 questionnaires were distributed and 210 of them were received. Usable responses were 170, comprising a response rate of 68 percent. From the results of the QFD application it is seen that behavior and attitude of staff has the highest weight score, meaning that when behavior and attitude of staff is improved there will be almost 25 per cent of improvement in the hospital. Another finding was that there is strong relationship among skills of physician, behavior and attitude of staff, and having enough modern equipment. QFD technique is able to provide hospitals with a better understanding of customers' expectations to translate these expectations into appropriate service specifications and perform existing process assessment. The case study was a first attempt to apply this integrative approach to a service sector and thus offers practical and applied information useful to both academicians and practitioners. © 2013, Emerald Group Publishing Limited
Keywords: Customer requirements; Health care; Private hospitals; Quality; Quality function deployment; SERVQUAL; Turkey